Beyond Productivity and Continuous Improvement: Fundamentals required for Lean Complex transformation Unpublished. Issue 12 (2016) - Leandro Elizondo, Ronald; Grabot, Bernard; Houe Ngouna, Raymond
Abstract: Lean Practices are well known and applied worldwide; their implementation purpose must be tailor-made because each firm is unique. There is a whole "management philosophy" behind it; its origins are based on Toyota's Just in Time (JIT) and perhaps cope with Deming's contributions. There is a heap of information on Lean; many practitioners coincides with their benefits likewise its complex deployment (non linear system). This paper reviews the literature concerning Lean management practices and the disability for some companies to uphold the results over time; specifically it analyses the difficulty to align Lean's implementation purpose (behaviour change) with the efforts to optimize processes within the organisation. The literature found two main reasons for this predicament: firstly a break down interaction between people (social side) and tools and techniques (technical side) and secondly, a lack of leadership commitment, especially from top managers. Therefore, the intention of this paper is to explain those pitfalls based on dynamic system thinking: the contribution of productivity improvement, which narrows in a more holistic manner these gaps. In addition, we focus on the continuous improvement approach as a metric to measure Lean's "behaviour change" and also to foster commitment (both leaders and human talent); the paper also tackles the performance problem through empowered workers that has been recognized in the Lean literature.